Cavitation control using Cylindrical Cavitating-bubble Generators (CCGs): Experiments on a benchmark CAV2003 hydrofoil. (April 2020) - Kadivar, Ebrahim; Timoshevskiy, Mikhail V.; Pervunin, Konstantin S.; Moctar, Ould el
Highlights: We studied a passive control method to stabilize the cloud cavitation instabilities using Cylindrical Cavitating-bubble Generators (CCGs). Experimental investigations of cavitation inception, sheet cavitation and cloud cavitations for the hydrofoil without and with CCGs were performed. Implemented passive cavitation control technique appeared to be quite effective method to suppress the cavitation in different cavitating flow regimes. Using our passive control method a notable reduction in the amplitude of pressure pulsations was observed. Abstract: Cavitation often causes a destructive impact on the performance of hydraulic machinery, such as erosive wear, noise and vibrations of the framework and moving parts of marine propellers, pumps, hydraulic turbines and other equipments, which eventually leads to a degradation of overall system effectiveness. The paper reports on an experimental investigation of a passive method of flow control for different cavitation conditions: starting from the cavitation inception, including quasi-steady partial cavitation with shedding of small-scale vortical structures and finishing by unsteady cloud cavitation. The passive flow control was implemented using miniature vortex generators of a cylindrical type referred to as Cylindrical Cavitating-bubble Generators (CCGs) that were placed on the surface of a benchmark CAV2003 hydrofoil. First, we performed high-speed visualization of cavitation on the suction side of the original hydrofoil (without the control element) to find the cavitation inception point near the leading edge and to analyze the spatial structure and time evolution of partial cavities. In order to improve our understanding of the mechanism of cavitating flow unsteadiness and the effect of CCGs on the cavitation dynamics, we also applied a PIV technique to measure the mean flow velocity profiles and a hydroacoustic pressure transducer to record local pressure pulsations in the hydrofoil wake. As a result, this allowed us to determine the influence of CCGs on turbulent structure of the flow at different cavitation regimes and amplitude-frequency spectra of the pressure pulsations associated with attached cavity length oscillations for unsteady flow conditions. It was revealed that, in the case of unsteady cloud cavitation, CCGs were capable to mitigate large-scale cloud cavities. In addition, a substantial decrease in the amplitude of pressure pulsations was registered for the modified hydrofoil (with the control element). In general, CCGs appeared to be quite effective to hinder the cavitation development and to reduce the strength of side- and middle-entrant jets as the primary mechanisms of unsteady cloud cavitation.